Oral Narrative Intervention by Tele-Practice in a Case with Developmental Language Disorder - Irina Iuliu; Verónica Martínez (MDPI AG, 2021)
Background: A narrative requires the integration and management of linguistic and cognitive skills. It has been observed that children with Developmental Language Disorder (DLD) have difficulties in narrating stories. This research proposes an intervention in a case of a child 9 years and 2 months old with DLD, with the aim of improving his oral narrative skills through a retelling task via telepractice. Methods: In the evaluation, standardized tests have been used and a 'remembering a story' task, with a story titled The Lost Backpack, elaborated by one of the authors. Narratives were elicited in two sessions, and were transcribed, coded, and analysed using the Child Language Data Exchange System CHILDES Project tool. The participant received a total of 10 sessions through the Skype platform, which included intervention-addressed explicit instruction about the narrative structure and the use of discourse markers to improve cohesion in story retelling. Results: Significant changes were observed in the retelling of the story at microstructure and macrostructure levels: an increase of the Mean Length of Utterance (MLU), Types and Tokens, specific vocabulary, discourse markers and the recall of events. Conclusions: These results demonstrate the effectiveness of intervention in narrative skills through the oral retelling of a story with visual support via tele-practice.